1995
DOI: 10.1073/pnas.92.2.402
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage foam cells from experimental atheroma constitutively produce matrix-degrading proteinases.

Abstract: Monocyte-derived foam cells figure prominently in rupture-prone regions of atherosclerotic plaques. Peripheral blood monocytes in culture can produce certain enzymes that degrade extracellular matrix, known as matrix metalloproteinases (MMPs). Lipid-laden macrophages may thus contribute to weakening of extracellular matrix of rupture-prone atherosclerotic plaques. However, the spectrum and regulation of MMP production by foam cells remain unknown. To investigate this issue, we isolated lipid-laden macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
277
0
9

Year Published

1998
1998
2007
2007

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 523 publications
(302 citation statements)
references
References 30 publications
(34 reference statements)
11
277
0
9
Order By: Relevance
“…These results are similar to those of previous studies using mature WHHL rabbits which su ered from established atherosclerosis treated with pravastatin alone (Shiomi et al, 1995) and in combination with cholestyramine (Shiomi et al, 1990). Davies et al (1993) reported that unstable plaques had large lipid cores, and Galis et al (1995) reported that macrophages secreted matrixdegradation proteinases, and collagen ®bres might be degraded. Therefore, reduction of atheromatous cores in the lesions is considered favourable with respect to stabilization of the plaque.…”
Section: Discussionsupporting
confidence: 90%
“…These results are similar to those of previous studies using mature WHHL rabbits which su ered from established atherosclerosis treated with pravastatin alone (Shiomi et al, 1995) and in combination with cholestyramine (Shiomi et al, 1990). Davies et al (1993) reported that unstable plaques had large lipid cores, and Galis et al (1995) reported that macrophages secreted matrixdegradation proteinases, and collagen ®bres might be degraded. Therefore, reduction of atheromatous cores in the lesions is considered favourable with respect to stabilization of the plaque.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have shown that infiltration of the graft by immune cells has generally occurred by day 5 after transplantation in rat models [ 151. Since neutrophils and macrophages are important producers of MMP-9 [12,26,271, the increase in proMMP-9 activity measured in the cortex and the medulla could thus be the result of immune cell infiltration. Active MMP-9 produced by neutrophils may be rapidly degraded by proteinases, under some circumstances, to limit further tissue damage [27].…”
Section: Discussionmentioning
confidence: 99%
“…33 Activated mast cells may be involved in tissue repair through the release of a wide variety of performed and newly synthesized mediators, such as the potent fibrogenic protease tryptase and a number of growth factors including basic fibroblast growth factors, vascular endothelial growth factor, and transforming growth factor-␤. 34 Both macrophages and mast cells are capable of producing matrix metalloproteinases, 35,36 critical factors in extracellular matrix metabolism. Accumulation of extracellular matrix proteins adversely affects myocardial viscoelasticity, leading to diastolic and systolic dysfunction.…”
Section: Macrophages and Mast Cells In Myocardial Fibrosismentioning
confidence: 99%